Employee Recruitment and Selection Procedures of NGOs in Bangladesh: A Study on BRAC - Ahmed, Rakib (Asian Business Review, 2013)
Recruitment and Selection is a foundation of Human Resource Management (HRM) practices and its integration to business is critical to achieve organisational strategic goals. Better recruitment and selection strategies result in improved organizational outcomes. The basic objective of this research is to explore the recruitment and selection procedures of NGOs based on BRAC; with analyzing these some recommendations are made to improve recruitment and selection practices. Here both primary and secondary sources are used for data collection and a structured questionnaire/ check lists was used to keep the research. The findings suggest that the largest NGOs emphasize professionalism and career orientations and implement long-term, forward looking approaches in their selection, recruitment, and remuneration. The small and mid-size NGOs, however, do not possess HR/ personnel management practices of their own; rather they follow and imitate larger members. The implications for HRM practitioners and scope for further research are discussed here.JEL Classification Code:  M500
Keywords: Recruitment; Selection; Bangladesh; NGOs; BRAC